2014
DOI: 10.1111/auar.12041
|View full text |Cite
|
Sign up to set email alerts
|

Audit Market Structure and Competition in Australia

Abstract: The purpose of this review is to synthesise the existing research literature regarding the underlying structure and competitiveness of the Australian audit market. We consider the findings of Australian academic research, which has examined audit fees, non-audit fees, market concentration, auditor choice, auditor switching and audit firm mergers. We identify the key metrics used to evaluate market structure in the academic literature and then document changes in these metrics in the Australian audit market for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 40 publications
0
35
0
2
Order By: Relevance
“…Nonetheless, the area has attracted a lot of attention in recent publications and is starting to emerge as one of the healthiest and most fruitful research streams. There are many emerging areas in audit research, including competition and pricing (Carson, ; Carson et al ., ; Ciconte et al ., ; Dutillieux et al ., ; Kend et al ., ; van der Laan and Christodoulou, ); the effects of regulatory change (Carey et al ., ; Houghton et al ., ; Lee et al ., ); trust (Howieson, ); reputation (Bigus, ); and audit judgement and decision making (Trotman et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the area has attracted a lot of attention in recent publications and is starting to emerge as one of the healthiest and most fruitful research streams. There are many emerging areas in audit research, including competition and pricing (Carson, ; Carson et al ., ; Ciconte et al ., ; Dutillieux et al ., ; Kend et al ., ; van der Laan and Christodoulou, ); the effects of regulatory change (Carey et al ., ; Houghton et al ., ; Lee et al ., ); trust (Howieson, ); reputation (Bigus, ); and audit judgement and decision making (Trotman et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…In a competitive audit market, auditors with superior service differentiation systematically charge higher fee for all their clients irrespective of their clients' size [24]. Audit market is competitive when Big N auditors differentiate their service to justify their fee premium in both large and small client segments [20]. On the other hand, audit market is not competitive when Big N firms charge higher fees in the large client market relative to smaller market segment [19].…”
Section: Audit Market Pricing Competitiveness: Big N Audit Fee Premiumentioning
confidence: 99%
“…The number of audit staff working on the audit engagement is employed to control for one of the major determinants of audit fee and audit effort. Carson et al (2014) argue that the observed increase of audit fees in Australian from 2000-2011 might be driven by higher audit effort that is driven by the global financial crisis and more stringent regulations [20]. Following Kim and Fukukawa (2013), the unique dataset of Japanese firms disclosure information is employed and natural log of number of CPAs, junior accountants and other staffs employed in the audit engagement (excluding engagement partners) is calculated (TEAM variable) [25].…”
Section: Audit Fee Determinants and Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…e papers refer to factors associated to rms in the audit market. As an example we can point to establishment of audit rms, studies related to audit rms (big audit rms and smaller ones), audit fees, fees awarded for audit services, factors concerning mandatory rotation of the Research in auditing: main themes audit rm, the monopoly of audit rms, and joint audit between audit rms (Caramanis, 2005;Carson, Redmayne, & Liao, 2014;Choi, Kim, Liu, & Simunic, 2008;De Franco, Gavious, Jin, & Richardson, 2011;Elliott, Ghosh, & Peltier, 2013). is theme had a result seven times higher and it is third in representativeness (27.6%), present during the whole project's period and in all journals.…”
Section: Established Themesmentioning
confidence: 99%